Preparation method and application of amphiphilic porous transmission layer
By hydrophobizing, laser cauterizing and hydrophilic treatment of the titanium-based material, an amphiphilic porous transport layer with an alternating hydrophilic-hydrophobic structure was prepared, which solved the problem that the reaction sites of the catalytic layer were easily covered by bubbles, achieved efficient transportation of gas and liquid, and improved the operating efficiency of electrolytic water and fuel cells.
Patent Information
- Application Number
- CN202411778337.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The reaction sites of the existing catalytic layer are easily covered by bubbles, resulting in the supply of liquid water being blocked and affecting the operation efficiency of electrolytic water and fuel cells.
By hydrophobizing the titanium-based material, laser sub-region cauterization and hydrophilic treatment, an amphiphilic porous transport layer with an alternating hydrophilic structure is prepared to achieve efficient transportation of gas and liquid.
This amphipathic porous transport layer can effectively reduce the mass transfer limitation of the electrolytic cell when operating at high current density, and improve the operating efficiency and long-term life of electrolytic water and fuel cells.
Smart Images

Figure CN119592978A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of proton exchange membrane water electrolysis, and in particular relates to a preparation method of an amphiphilic porous transport layer and application thereof. Background Art
[0002] As a key component of PEM electrolyzer / fuel cell, the porous transport layer (PTL) is one of the key components of the cost and performance of PEM electrolyzer / fuel cell, playing the role of reactant distribution, product discharge, conductivity, support, etc. During the operation of the PEM electrolyzer, the PTL on the anode side is in a complex environment of high pressure, strong corrosion, and gas-liquid two phases. Therefore, titanium-based materials with good corrosion resistance (such as titanium felt, titanium mesh, sintered titanium plate) are often used as the porous transport layer on the anode side.
[0003] However, with the long-term operation of the electrolytic cell, titanium materials will also suffer from degradation phenomena such as hydrogen embrittlement and passivation, which will reduce the life of the porous transport layer and the performance of the electrolytic cell. In the optimization direction of the porous transport layer, the current mainstream research focuses on optimizing the conductive properties and improving durability. The modification methods are mainly based on precious metal coatings such as platinum and gold, which are costly and complex.
[0004] Considering that the liquid water supply and generated oxygen discharge in the anode side PTL are in a countercurrent material transfer state, it is very easy to cause bubbles to accumulate and block in the PTL, which in turn leads to the reaction sites of the catalyst layer being covered by accumulated bubbles and the liquid water supply being blocked. Therefore, regulating the PTL from the perspective of optimizing material transfer is a novel and efficient research idea. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a method for preparing an amphiphilic porous transport layer, which aims to solve the problem that the reaction sites of the existing catalytic layer are easily covered by accumulated bubbles and the supply of liquid water is blocked. The present invention also provides the application of the amphiphilic porous transport layer in the fields of water electrolysis and fuel cells.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing an amphiphilic porous transport layer comprises the following steps:
[0008] 1) subjecting the titanium-based material to a hydrophobic treatment to obtain a hydrophobic titanium-based material;
[0009] 2) performing laser burning treatment on the hydrophobic titanium-based material obtained in step 1);
[0010] 3) The titanium-based material subjected to the calcination treatment in step 2) is subjected to a hydrophilic treatment to obtain an amphiphilic porous transport layer.
[0011] In some specific embodiments, the titanium-based material is one of titanium felt, titanium mesh or sintered titanium plate.
[0012] Furthermore, the titanium-based material is titanium felt; because titanium felt has the characteristics of high porosity, low contact resistance, and excellent mechanical properties compared to titanium mesh or titanium plate, and thus, during laser processing, the titanium felt base material will hardly produce thermal deformation and ablation oxidation, which provides technical support for the use of laser processing for the transmission layer.
[0013] In some specific embodiments, the titanium-based material in step 1) is pretreated, specifically: the titanium-based material is ultrasonically cleaned in acetone, ethanol, and deionized water, and then vacuum dried for standby use. The pretreatment process is mainly to remove grease and other impurities on the purchased titanium felt, and the vacuum drying is mainly to prevent oxidation of the titanium felt.
[0014] In some specific embodiments, the hydrophobic treatment in step 1) is specifically: immersing the pretreated titanium-based material in a hydrophobic agent, taking out and drying after the surface of the titanium-based material is evenly coated with a layer of hydrophobic agent, and then heating and curing to obtain a hydrophobic titanium-based material;
[0015] Furthermore, the hydrophobic agent is a PTFE solution, and the mass concentration of the PTFE solution is 2-10%;
[0016] In some specific embodiments, the burning treatment in step 2) is specifically to fix the hydrophobic titanium-based material on a laser marking platform, and to perform laser burning on the hydrophobic titanium-based material according to the set burning area to obtain a laser-burned titanium-based material; after the laser-burned titanium-based material, the PTFE attached to the titanium felt is removed to expose the titanium felt base underneath.
[0017] Furthermore, the laser is a picosecond laser, and the high-speed thermal effect of the picosecond laser is used to remove the PTFE on the surface of the titanium felt, which can ensure that the thermal stress is not caused to the surface of the titanium felt material while the PTFE on the titanium felt is removed.
[0018] Furthermore, the burnt area can be stripes of different widths, different shapes, and different arrangements; in order to obtain amphiphilic titanium felts of different burnt shapes and different burnt sizes, the shapes of the burnt areas are set to: stripe, grid, and circle; wherein the burnt width of the stripe is 100 μm, and the burnt intervals are 50 μm, 100 μm, 200 μm, and 300 μm, respectively, and the stripes remain parallel during burnt; the burnt width of the grid is 50 μm, 100 μm, and The burning interval and the burning width are kept the same (50μm, 100μm, 200μm), the stripes are kept parallel during burning, and the titanium felt is rotated 90° after burning and fixed on the processing table for processing again (the parameters remain unchanged) to form a mesh structure with perpendicular stripes; the circular burning diameter is 100μm, and the center distances of each burned circular area are 150μm, 200μm, and 300μm respectively, and the upper and lower center distances of adjacent burned circles are the same.
[0019] In some specific embodiments, the hydrophilic treatment in step 3) is specifically: placing the laser-burned titanium-based material in an acidic solution for etching, followed by cleaning and drying to obtain an amphiphilic porous transport layer.
[0020] Furthermore, the method further includes ultrasonically cleaning the laser-burned titanium-based material in acetone, ethanol, and deionized water to remove residual PTFE on the burned surface, and then placing the material in a vacuum drying oven to dry after thorough cleaning.
[0021] In some specific embodiments, the process parameters of the etching treatment are: etching for 15-25 minutes in a water bath at 60-100° C. The etching treatment converts the laser-burned area of the titanium-based material into a hydrophilic property, and the titanium-based material is placed in an oxalic acid solution and heated, and the laser-burned titanium felt area is converted into a rougher structure by utilizing the acid etching properties of oxalic acid. According to the Wenzel equation, the hydrophilicity of the originally slightly hydrophilic burnt surface increases as the roughness further increases.
[0022] An amphiphilic porous transport layer obtained by the above preparation method.
[0023] An application of the aforementioned amphiphilic porous transport layer in the fields of water electrolysis and fuel cells.
[0024] Compared with the prior art, the present invention has at least the following advantages:
[0025] 1) The preparation method of the amphiphilic porous transport layer provided in the present application combines laser processing technology with PTFE impregnation hydrophobic modification technology to construct an amphiphilic porous transport layer with a hydrophilic-hydrophobic alternating structure, which can achieve efficient transport of gases and liquids and improve the operating efficiency of water electrolysis to produce hydrogen and fuel cells.
[0026] 2) The preparation method of the amphiphilic porous transport layer provided by the present invention constructs an amphiphilic titanium felt through laser processing, which has the characteristics of small heat-affected area, high processing efficiency and low cost; at the same time, through laser processing, it is also possible to freely set the burning parameters such as different shapes, different spacings, and different stripe widths, thereby constructing a patterned amphiphilic structure titanium felt with high degree of freedom of customization.
[0027] 3) The amphiphilic porous transport layer prepared by the present invention has a hydrophilic-hydrophobic alternating structure, which can realize the separate-path transport of liquid water and oxygen in the titanium felt. Liquid water and oxygen are efficiently discharged through the hydrophilic area and the hydrophobic area respectively, which greatly reduces the mass transfer limitation of the electrolytic cell operating at high current density and improves the long-term operating life of the electrolytic cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0029] Figure 1 A microscopic morphology structure diagram of an amphiphilic porous transmission layer with a hydrophilic-hydrophobic alternating arrangement structure based on hydrophobicization treatment and laser ablation treatment provided in Example 2 of the present invention;
[0030] Figure 2 Comparison of current-voltage curves of an amphiphilic porous transport layer with a hydrophilic-hydrophobic alternating arrangement structure based on laser processing and PTFE hydrophobic treatment provided in Example 2 of the present invention;
[0031] Figure 3 The contact angle (wettability) test results of the hydrophobic and hydrophilic regions of an amphiphilic porous transmission layer with a hydrophilic-hydrophobic alternating arrangement structure based on laser processing and PTFE hydrophobic treatment provided in Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0033] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0034] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0035] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0036] In the following embodiments, titanium felt is selected as the titanium-based material, and the titanium felt adopts the mainstream commercial original titanium felt on the market as the modified material, with a porosity between 60-70% and a thickness of 250 μm; the oxalic acid is 98% pure oxalic acid crystals, which are ground and added with deionized water to form an oxalic acid solution with a concentration of 10 wt.%; the commercial titanium felt used is TA1 grade titanium alloy, and the titanium content is ≥99.5%;
[0037] Example 1
[0038] This embodiment provides a method for preparing an amphiphilic porous transport layer, which comprises the following steps:
[0039] 1) Preprocessing
[0040] The titanium felt was cut into a size of 2.6 cm × 2.6 cm by laser cutting. Before subsequent treatment, the titanium felt was first ultrasonically cleaned in acetone, ethanol, and deionized water for 10 min to remove surface impurities, and then placed in a vacuum drying oven to dry thoroughly for use;
[0041] 2) Hydrophobic treatment
[0042] The pretreated titanium felt was impregnated with a PTFE emulsion with a mass fraction of 3%, and was allowed to stand for 30 minutes to wait for the titanium felt to be completely impregnated. The impregnated titanium felt was then purged with nitrogen and vacuum dried, and then the PTFE impregnation and drying steps were repeated until the mass fraction of PTFE in the titanium felt reached 3%; finally, the impregnated and dried titanium felt was placed in a tubular furnace in a nitrogen atmosphere at 350°C for heating, and the heating time was set to 30 minutes, so that the PTFE was high-temperature solidified on the titanium felt to form a hydrophobic titanium felt with a stable chemical structure;
[0043] 3) Burning treatment
[0044] The hydrophobic titanium felt obtained in step 2) is fixed on a laser marking platform, and according to the set burning area, the hydrophobic titanium felt is laser processed on the surface of the hydrophobic titanium felt using a UV picosecond laser marking machine. After the front side of the titanium felt is processed, it is turned over, and the processed area overlaps with the other side, and the back side is processed. The processing parameters are consistent with the front side to obtain a laser-burned titanium felt;
[0045] Among them, during the laser processing, the parameters of the laser processing system are: marking times 4; laser Q frequency 70KHz; laser Q release 7μs; processing area 26mm*26mm, marking speed 1800mm / s, jump speed 1500mm / s, current 2.5A;
[0046] The burning area is set, specifically, the shape of the burning area is stripe-shaped, the burning width of the stripe-shaped is 100 μm, the burning interval is 200 μm, and the stripes are kept parallel during burning;
[0047] 4) Acid etching
[0048] The titanium felt that has been laser-burned in step 3) was ultrasonically cleaned in acetone, ethanol and deionized water for 10 minutes respectively to remove impurities introduced during the processing, and then placed in a vacuum drying oven to be thoroughly dried.
[0049] An oxalic acid solution with a mass concentration of 10wt.% was heated to 60°C in a water bath, and the titanium felt after the calcination treatment after impurities were removed was placed in the oxalic acid solution for etching for 25 minutes, and then fully rinsed with ultrapure water and vacuum dried to obtain an amphiphilic porous transport layer.
[0050] Example 2
[0051] This embodiment provides a method for preparing an amphiphilic porous transport layer, which comprises the following steps:
[0052] 1) Preprocessing
[0053] The titanium felt was cut into a size of 2.6 cm×2.6 cm by laser cutting. Before subsequent treatment, the titanium felt was first ultrasonically cleaned in acetone, ethanol, and deionized water for 10 min to remove surface impurities, and then placed in a vacuum drying oven to be thoroughly dried for later use.
[0054] 2) Hydrophobic treatment
[0055] The pretreated titanium felt was impregnated with a PTFE emulsion with a mass fraction of 5%, and was allowed to stand for 30 minutes to wait for the titanium felt to be completely impregnated. The impregnated titanium felt was then purged with nitrogen and vacuum dried, and then the PTFE impregnation and drying steps were repeated until the mass fraction of PTFE in the titanium felt reached 5%; finally, the impregnated and dried titanium felt was placed in a tubular furnace in a nitrogen atmosphere at 350°C for heating, and the heating time was set to 30 minutes, so that the PTFE was solidified at high temperature on the titanium felt to form a hydrophobic titanium felt with a stable chemical structure;
[0056] 3) Burning treatment
[0057] The hydrophobic titanium felt obtained in step 2) is fixed on a laser marking platform, and according to the set burning area, the hydrophobic titanium felt is laser processed on the surface of the hydrophobic titanium felt using a UV picosecond laser marking machine. After the front side of the titanium felt is processed, it is turned over, and the processed area overlaps with the other side, and the back side is processed. The processing parameters are consistent with the front side to obtain a laser-burned titanium felt;
[0058] Among them, during the laser processing, the parameters of the laser processing system are: marking times 4; laser Q frequency 70KHz; laser Q release 7μs; processing area 26mm*26mm, marking speed 1800mm / s, jump speed 1500mm / s, current 2.5A;
[0059] The burning area is set, specifically: the shape of the burning area is a grid shape, and the burning width of the grid shape is 200 μm, the burning interval is kept the same as the burning width (200 μm), the stripes are kept parallel during burning, and after burning, the titanium felt is rotated 90° and fixed on the processing table again for processing (the parameters remain unchanged) to form a mesh structure with stripes perpendicular to each other;
[0060] 4) Acid etching
[0061] The titanium felt that has been laser-burned in step 3) was ultrasonically cleaned in acetone, ethanol and deionized water for 10 minutes respectively to remove impurities introduced during the processing, and then placed in a vacuum drying oven to be thoroughly dried.
[0062] An oxalic acid solution with a mass concentration of 10wt.% was heated to 80°C in a water bath, and the titanium felt after the calcination treatment after the impurities were removed was placed in the oxalic acid solution for etching for 20 minutes, and then fully rinsed with ultrapure water and vacuum dried to obtain an amphiphilic porous transport layer.
[0063] Example 3
[0064] This embodiment provides a method for preparing an amphiphilic porous transport layer, which comprises the following steps:
[0065] 1) Preprocessing
[0066] The titanium felt was cut into a size of 2.6 cm × 2.6 cm by laser cutting. Before subsequent treatment, the titanium felt was first ultrasonically cleaned in acetone, ethanol, and deionized water for 10 min to remove surface impurities, and then placed in a vacuum drying oven to dry thoroughly for use;
[0067] 2) Hydrophobic treatment
[0068] The pretreated titanium felt was impregnated with a PTFE emulsion with a mass fraction of 10%, and was allowed to stand for 30 minutes to wait for the titanium felt to be completely impregnated. The impregnated titanium felt was then purged with nitrogen and vacuum dried, and then the PTFE impregnation and drying steps were repeated until the mass fraction of PTFE in the titanium felt reached 10%; finally, the impregnated and dried titanium felt was placed in a tubular furnace in a nitrogen atmosphere at 350°C for heating, and the heating time was set to 30 minutes, so that the PTFE was solidified at high temperature on the titanium felt to form a hydrophobic titanium felt with a stable chemical structure;
[0069] 3) Burning treatment
[0070] The hydrophobic titanium felt obtained in step 2) is fixed on a laser marking platform, and according to the set burning area, the hydrophobic titanium felt is laser processed on the surface of the hydrophobic titanium felt using a UV picosecond laser marking machine. After the front side of the titanium felt is processed, it is turned over, and the processed area overlaps with the other side, and the back side is processed. The processing parameters are consistent with the front side to obtain a laser-burned titanium felt;
[0071] Among them, during the laser processing, the parameters of the laser processing system are: marking times 4; laser Q frequency 70KHz; laser Q release 7μs; processing area 26mm*26mm, marking speed 1800mm / s, jump speed 1500mm / s, current 2.5A;
[0072] The burn area is set, specifically, the shape of the burn area is circular, the burn diameter of the circle is 100 μm, the center distance of each burnt circular area is 200 μm, and the upper and lower center distances of adjacent burnt circles are the same;
[0073] 4) Acid etching
[0074] The titanium felt that has been laser-burned in step 3) was ultrasonically cleaned in acetone, ethanol and deionized water for 10 minutes respectively to remove impurities introduced during the processing, and then placed in a vacuum drying oven to be thoroughly dried.
[0075] An oxalic acid solution with a mass concentration of 10wt.% was heated to 100°C in a water bath, and the titanium felt after the calcination treatment after impurities were removed was placed in the oxalic acid solution for etching for 15 minutes, and then fully rinsed with ultrapure water and vacuum dried to obtain an amphiphilic porous transport layer.
[0076] Comparative Example 1
[0077] The present invention provides a method for preparing a porous transmission layer, and the preparation method is basically the same as that of Example 2, except that only the titanium felt is acid-etched, specifically:
[0078] 1) Preprocessing
[0079] The titanium felt was cut into a size of 2.6 cm × 2.6 cm by laser cutting. Before subsequent treatment, the titanium felt was first ultrasonically cleaned in acetone, ethanol, and deionized water for 10 min to remove surface impurities, and then placed in a vacuum drying oven to dry thoroughly for use;
[0080] 2) Etching treatment
[0081] The oxalic acid solution with a mass concentration of 10wt.% is heated to 80°C in a water bath, and the pretreated titanium felt is placed in the oxalic acid solution for etching for 20 minutes, and then fully rinsed with ultrapure water and vacuum dried to obtain a porous transmission layer;
[0082] Performance Testing:
[0083] This application takes Example 2 as an example, and performs a performance test on the porous transmission layer prepared in Example 2 while introducing commercial original titanium felt (titanium felt that has not been treated in any way), specifically:
[0084] 1) Electrochemical test
[0085] Test method: During the electrochemical test, the amphiphilic titanium felt was placed on the anode side of the electrolytic cell, and deionized water was passed into the electrolytic cell using a peristaltic pump. The flow rate was set to 5 mL / min and the water temperature was 80 °C. After the membrane electrode was fully activated for 2 hours, a DC power supply was used to continue electroactivation at a constant voltage of 1 V for 30 minutes. After the electrolytic cell was stabilized, the current density was 0-3 A / cm 2 The electrolytic cell was tested for linear sweep voltammetry (LSV) within the range of 0.1A / cm. The polarization curve was tested at a certain step length, 0-0.1A / cm 2 Select 0.01A / cm 2 Step size, 0.1-2A / cm 2 Select 0.1A / cm 2 Step length, 2-3A / cm 2 Select 0.2A / cm within the current density range 2 The step size was set to 2 min at each current density to ensure accurate and stable data.
[0086] 2) Results and Discussion
[0087] The results are as follows Figure 2 and Figure 3 As shown, Figure 2 The voltage and mass transfer loss of titanium felt are shown in the LSV test curve: 2 At low current density, except for the titanium felt treated with PTFE, the voltage growth trend of the other titanium felts remained the same. The voltage of the titanium felt treated with PTFE hydrophobic treatment was 0.3A / cm 2 A surge occurs when the 2 The voltage is 1.85V at a current density of 1A / cm, which is 140mV higher than that of untreated commercial titanium felt. 2 To 2A / cm 2 At a medium current density of 2.5A / cm2, the voltage of the PTFE hydrophobic treated titanium felt surged to 2.5V, and the mass transfer in the electrolytic cell deteriorated seriously. In comparison, the voltage growth of the other three groups of titanium felts at medium current density was relatively slow, and the cell voltage of the amphiphilic titanium felt was 60mV lower than that of the original untreated commercial titanium felt. When the current density reached 2-5A / cm2, the voltage of the PTFE hydrophobic treated titanium felt increased significantly, and ... decreased by 60mV. When the current density reached2 In the high current density range, the advantages of amphiphilic titanium felt begin to emerge. 2 The voltage is 1.81V, which is 110mV lower than that of untreated commercial titanium felt. 2 When the amphiphilic titanium felt is treated with oxalic acid, the voltage of the amphiphilic titanium felt is only 2.28 V, which is 260 mV lower than that of the untreated commercial titanium felt. Moreover, there is no voltage surge phenomenon as in the case of the commercial titanium felt treated with oxalic acid hydrophilicity (Comparative Example 1).
[0088] The above results prove that the alternating wettability structure of hydrophilic-hydrophobic can effectively reduce the cell voltage and avoid the voltage surge phenomenon when the electrolytic cell is running at a high current density; at the same time, the amphiphilic porous transport layer of the present application has lower mass transfer loss and higher wettability contrast (such as Figure 3 As shown); that is, the proton exchange membrane water electrolysis system based on the amphiphilic titanium felt prepared in this application has lower energy consumption, thereby reducing the cost of hydrogen production and improving the efficiency of hydrogen production by water electrolysis.
[0089] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing an amphiphilic porous transport layer, characterized in that: The steps include: 1) subjecting the titanium-based material to a hydrophobic treatment to obtain a hydrophobic titanium-based material; 2) performing laser burning treatment on the hydrophobic titanium-based material obtained in step 1); 3) The titanium-based material subjected to the calcination treatment in step 2) is subjected to a hydrophilic treatment to obtain an amphiphilic porous transport layer.
2. The method for preparing the amphiphilic porous transport layer according to claim 1, characterized in that: The titanium-based material is one of titanium felt, titanium mesh or sintered titanium plate.
3. The method for preparing an amphiphilic porous transport layer according to claim 1 or 2, characterized in that: The method further includes pre-treating the titanium-based material in step 1), specifically, ultrasonically cleaning the titanium-based material in acetone, ethanol, and deionized water, respectively, and vacuum drying the titanium-based material after cleaning for later use.
4. The method for preparing an amphiphilic porous transport layer according to claim 3, characterized in that: The hydrophobic treatment in step 1) is specifically as follows: immersing the pretreated titanium-based material in a hydrophobic agent, taking out and drying after the surface of the titanium-based material is evenly coated with a layer of hydrophobic agent, and then heating and curing to obtain a hydrophobic titanium-based material.
5. The method for preparing an amphiphilic porous transport layer according to claim 4, characterized in that: The hydrophobic agent is a PTFE solution, and the mass concentration of the PTFE solution is 2-10%.
6. The method for preparing an amphiphilic porous transport layer according to claim 4, characterized in that: The burning treatment in step 2) is specifically to fix the hydrophobic titanium-based material on the laser marking platform, and to perform laser burning on the PTFE according to the set burning area to obtain the laser-burned titanium-based material.
7. The method for preparing an amphiphilic porous transport layer according to claim 5, characterized in that: The hydrophilic treatment in step 3) is specifically as follows: placing the laser-burned titanium-based material in an acidic solution for etching, followed by cleaning and drying to obtain an amphiphilic porous transport layer.
8. The method for preparing an amphiphilic porous transport layer according to claim 7, characterized in that: The process parameters of the etching treatment are: etching for 15-25 minutes in a water bath at 60-100°C.
9. An amphiphilic porous transport layer obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the amphiphilic porous transport layer according to claim 9 in the fields of water electrolysis and fuel cells.
Citation Information
Cited By
Gas-liquid transmission layer with special gas-liquid transmission structure
CN120291110A
Porous transmission layer and preparation method thereof
CN121183358A